Cost-Effectiveness Analysis of Implantable Cardioverter Defibrillator Therapy for Primary Prevention Patients with Additional Risk Factors in Brazil - Wherry,Kael (2021)
Abstract Background: Implantable cardiac defibrillators (ICDs) therapy for primary prevention (PP) of sudden cardiac arrest (SCA) is well-established but underutilized globally. The Improve SCA study has identified a cohort of patients called 1.5 primary prevention (1.5PP), based on PP patients with the presence of documented risk factors: non-sustained ventricular tachycardia, frequent premature ventricular contractions, left ventricular ejection fraction < 25%, and pre-syncope or syncope. Objective: This study evaluated the cost-effectiveness of ICD therapy compared to no ICD among 1.5PP patients in the Brazilian public healthcare system. Methods: Modified inputs to a published Markov model were applied to compare costs and outcomes of ICD therapy to no ICD therapy from the Brazilian payer’s perspective. Mortality and utility estimates were obtained from the IMPROVE SCA trial. Additional effectiveness inputs were sourced from the literature. Cost inputs were obtained from the Brazilian Unified Health System and the Ministry of Health. Costs were discounted at 4.7%; quality-adjusted life years (QALYs) were discounted at 1.45%. This study applied a willingness-to-pay (WTP) value of three times Brazil’s gross domestic product (GDP) in 2017, R$105,723 (Brazilian Real). Results: The total discounted lifetime costs for ICD therapy were R$100,920 compared to R$43,866 for no ICD therapy. Total discounted QALYs for ICD therapy and no ICD therapy were 9.85 and 7.15, respectively. The incremental cost effectiveness ratio was R$21,156 per QALY and less than the R$105,723 WTP threshold. Results from sensitivity analyses were consistent with base case results. Conclusions: ICD therapy compared to no ICD therapy is cost-effective in the 1.5PP population in Brazil. (Int J Cardiovasc Sci. 2021; [online].ahead print, PP.0-0)